Thermodynamic response of an ultrasonic densitometer - Higuti, R. T. [UNESP]; Galindo, B. S. [UNESP]; Kitano, C. [UNESP]; Buiochi, F.; Adamowski, J. C. (My University, 2005)
An ultrasonic densitometer is experimentally characterized as a function of temperature. The measurement of propagation velocity and density of several liquids is performed in the 15 to 40°C temperature range. Results are compared to tabulated values in the case of distilled water, showing accuracy of 0.07% for the propagation velocity. Density values are compared to those obtained with a pycnometer, showing 0.2% accuracy in density measurement for stabilized temperature and 0.4% under thermal gradient conditions.
Keywords: Density value; Distilled water; Propagation velocities; Temperature range; Densitometers; Meteorological instruments; Density of liquids